Concentration-dependent effect of plant secondary metabolites on bacterial and fungal microbiomes in caterpillar guts - Šigutová, Hana; Pyszko, Petr; Šigut, Martin; Czajová, Kateřina; Kostovčík, Martin; Kolařík, Miroslav; Hařovská, Denisa; Drozd, Pavel (Microbiology spectrum, 2024)
The caterpillar gut is an excellent model system for studying host-microbiome interactions, as it represents an extreme environment for microbial life that usually has low diversity and considerable variability in community composition. Our study design combines feeding caterpillars on a natural and artificial diet with controlled levels of plant secondary metabolites and uses metabarcoding and quantitative PCR to simultaneously profile bacterial and fungal assemblages, which has never been performed. Moreover, we focus on multiple caterpillar species and consider diet breadth. Contrary to many previous studies, our study suggested the functional importance of certain microbial taxa, especially bacteria, and confirmed the previously proposed lower importance of fungi for caterpillar holobiont. Our study revealed the lack of differences between monophagous and polyphagous species in the responses of microbial assemblages to plant secondary metabolites, suggesting the limited role of the microbiome in the plasticity of the herbivore diet.
Keywords: rostliny; Plants; Microbiota; bacterial and fungal microbiomes; Bacteria; network stability; salicylic acid; plant secondary metabolite; invertebrate–microbe interactions; Mycobiome; tannivin; tannin; mykobiom; mikrobiota